Synthesis and reactivity of [3.1.1]propellane - Frank, N (2022)
In this thesis, the question about reactivity and character of a higher propellane, [3.1.1]Propellane (TCHep), is posed which was so far only synthesised on milligram scale. Chapter 1 gives an introduction into strained molecules, especially the reactivity of the well-explored [1.1.1]propellane and bioisosteres in a medicinal chemistry context. In Chapter 2 a novel multigram scale synthesis of TCHep is developed. This made exploration of the chemistry of TCHep possible for which a scope on a variety of reliable reactions is prepared yielding bridgeheaded substituted bicyclo[3.1.1]heptanes (BCHep). Chapter 2 continues with computational and mechanistic approaches to decipher characteristic differences between TCP and TCHep. Chapter 3 recognises that the BCHep substitution pattern maps precisely onto the geometry of meta-substituted benzenes. Functionalisation reactions of BCHep iodides were explored. The BCHep-pharmaceutical analogues of Sonidegib and URB597 were prepared. These drugs revealed enhanced ADME properties to their parent drugs, validating the potential of this meta-arene analogue as an sp3-rich motif in drug design.